Auditors’ job performance: the effects of job autonomy and role ambiguity / Syed Redzwan Sayed Rohani - Sayed Rohani, Syed Redzwan (2013)
This study examines the relationship of several perceived characteristics of the work environment among auditors working for big public accounting firms. Specifically, the study explores the relationship of job autonomy and role ambiguity to auditors’ job performance. The sample consists of 150 existing auditors who work with the big four auditing firms in Klang Valley. A total of 90 responses are used for further analysis. It is hypothesized that job autonomy should have a positive relationship with auditors’ job performance. While it is predicted that role ambiguity should have a negative relationship with auditors’ job performance. The regression results suggest that job autonomy is statistically significant and is positively associated with auditors’ job performance. Conversely, role ambiguity is found to have a significant and negative relationship with auditors’ job performance. The information obtained from this study should be useful to the managers and policy makers of an audit firm so that they could be more sensitive and alert to the indicator of Malaysian auditors’ performance. Further study in this area should include other possible determinant and larger samples of Malaysia auditors that consists of big, medium and small size audit firms in order to get a more robust picture on the auditors’ job performance.